2020
DOI: 10.3390/jcm9072160
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach for Improving Quality of Life and Self-Management in Diabetic Kidney Disease: A Crossover Study

Abstract: Individuals with diabetic kidney disease are at high risk of complications and challenged to self-manage. Previous research suggested that multidisciplinary approaches would improve health outcomes. This study investigated the effect of a multidisciplinary self-management approach of diabetic kidney disease on quality of life, and self-management, glycemic control, and renal function. A uniform balanced crossover design was used because it attains a high level of statistical power with a lower sample s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…An integrated, multidisciplinary intervention program supported that integrated care could be useful for managing difficult‐to‐control chronic hand eczema patients 8 . Previous research has also shown multidisciplinary management of chronic disease can improve patient outcomes, 9 particularly in difficult‐to‐control complex multi‐organ disease 10–13 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An integrated, multidisciplinary intervention program supported that integrated care could be useful for managing difficult‐to‐control chronic hand eczema patients 8 . Previous research has also shown multidisciplinary management of chronic disease can improve patient outcomes, 9 particularly in difficult‐to‐control complex multi‐organ disease 10–13 …”
Section: Discussionmentioning
confidence: 98%
“…8 Previous research has also shown multidisciplinary management of chronic disease can improve patient outcomes, 9 particularly in difficult-to-control complex multi-organ disease. [10][11][12][13] Principles of SDM are well documented 14 and SDM can lead to an improved physician-patient relationship from patients' and doctors' perspectives. 15 Utilization of SDM has been successful in improving patient perception of care as evidenced by significant improvements in PROs as well as successful disease management.…”
Section: Discussionmentioning
confidence: 99%
“…Resultados semelhantes ocorreram em estudo randomizado que comparou a adesão ao tratamento anti-hipertensivo de pacientes submetidos ao atendimento convencional, com aqueles atendidos por equipe multidisciplinar. Todavia, o intervalo entre as abordagens e a forma de avaliação do grau de adesão, foram diferentes (MEMS) (HELOU et al, 2020).…”
Section: Discussionunclassified
“…Examples of collaboration in quality improvement studies include speech pathologists looking at effective medication management of patients with dysphagia, and staff specialists in neonatology looking at effective and safe antihypertensive agents in critically ill infants. There is substantial evidence that a multidisciplinary approach to delivering health care is essential to delivery of best patient outcomes [ 12 , 13 ]. The same approach should be considered when undertaking quality improvement or research studies, to ensure robust design as well as effective implementation and evaluation.…”
Section: Discussionmentioning
confidence: 99%